Rvhe ti guṃ sutesana cā coṅʻ = Researches on the Shwedagon Pagoda (Praññʻ thoṅʻ cu Chuirhayʻlacʻ Sammata Mranʻ mā Nuiṅʻ ṅaṃ toʻ, Yañʻ kyeʺ mhu Vanʻ krīʺ Ṭhāna, Nuiṅʻ ṅaṃ Samuiṅʻʺ Sutesana Ūʺ cīʺ Ṭhāna, 1980)
Researches on a Buddhist shrine in Rangoon, Burma.